Biosensor Using Accelerometer for Cardiac Cycle Monitoring - Phạm Ngọc Sơn; Đinh Vân Anh (Journal of Technical Education Science, 2012)
A biosensor is developed to monitor cardiac function to be used in e-health and clinical medicine (screening and diagnosis). The sensor uses a tri-axial accelerometer to record the ultra low- frequency vibrations of the heart. Appropriate filtering and amplification were built to provide a seismocardiograph which represents the heart activity. The signals are then digitized and stored in a SD card for later analysis or sent over a wireless communications link to a smartphone for real time monitoring. The development of such device can become an easy-to-use cardiac screening tool which has a potential impact in cardiovascular health.